The Role of Accounting Digitalization in Enhancing the Effectiveness of Corporate Tax Planning - Saputra, Asep (Journal Research of Social Science, Economics, and Management, 2026)
Digitization of accounting is one of the important factors in increasing the effectiveness of corporate tax planning in the era of digital transformation. This research aims to analyze the role of accounting digitization in supporting more effective and efficient tax planning. The research method used is a qualitative approach with a descriptive design through literature study and conceptual analysis of the implementation of digital accounting technology. The results of the study show that accounting digitization is able to improve the quality of financial information through a real-time, integrated, and accurate system, thereby accelerating the process of preparing tax reports, reducing the error rate, and increasing compliance with tax regulations. In addition, the use of technology such as ERP, cloud accounting, big data analytics, and artificial intelligence allows companies to conduct tax analysis more comprehensively and predictively. However, the implementation of digitalization still faces challenges in the form of high investment costs, limited human resources, and data security risks. This study concludes that accounting digitalization has a strategic role in increasing the effectiveness of tax planning, both in terms of operational efficiency and more optimal tax decision-making.